Denunciações e confissões em ritos de alteridade: o santo inquerito de Dias Gomes - Cerqueira, Patricia Conceição Borges Franca Fialho (2007)
This work studies the play O Santo Inquérito (The Holy Inquiry), by the Bahian writer Dias Gomes, that is situated between fiction and history, and rotates around the prison and execution of Branca Dias by the Sacred Office Tribunal. It can also be read in an allegorical way as an angry denunciation on the part of the author against the generalized repression that was felt in Brazil after the military coup, in 1964. That is due to the existent similarities between the systems once both, the Inquisition and the Dictatorship, represent an extremely hegemonic, authoritarian and centralizing power. This way, this study aims to analyze in which ways the judgement and condemnation of Branca Dias happened due to religious intolerance and also to the intolerance to thought alterity, as well as to verify in what way that intolerance is established against those who, somehow, are opposed to the pre-established systems. Although it is a play, the text in question will be analyzed as literature, giving the main focus to the words, to the literary narrative. Also the philosophical and historical approach of the treated subjects should be done in order to contextualize and emerge the necessary elements for the good understanding of the text. The methodology used has as main resource the bibliographical research of the theoretical and informative bases, and also of researchers and historians of the approached themes, which will give the necessary support for the analysis of the dramatic play O Santo Inquérito (The Holy Inquiry) inside the proposed requirements.